Genetic variation of classical swine fever virus based on palindromic nucleotide substitutions, a genetic marker in the 5' untranslated region of RNA - Massimo Giangaspero; Ryô Harasawa (Veterinaria Italiana, 2008)
Forty-three strains of classical swine fever (hog cholera) virus (CSFV) from outbreaks in pigs in Europe, Asia and America, two strains from commercial CSFV modified live vaccines and a strain isolated from a diseased lamb from Spain were subjected to analyses of nucleotide sequence variations in the 5’ terminal region of the genome. These isolates were divided into three clusters, namely: CSFV-1, CSFV-2, and CSFV-3, based on palindromic nucleotide substitutions in the 5’ untranslated region (UTR). The homology degree, according to nucleotide base pairing variation in the secondary palindromic structure of the three variable loci V1, V2 and V3, was 60% in the CSFV species, with a mean divergence value of 6.19 base pairs (bp). relatedness within genotypes ranged from 71.11% to 100%, with mean divergence values from 5.5 to 0.73 base pairs. Subgenotypes showed a divergence ranging from 1 to 9 base pairs within the genotype. Genotype CSFV-1 revealed 15 base pair combinations with 13 divergent base pairs, resulting in 4 subgenotypes with 6 variants in subgenotype CSFV-1.1, including the reference strain Brescia and 6 variants in subgenotype CSFV-1.2, including the Alfort reference strain. Subgenotypes CSFV-1.3 and CSFV-1.4 comprised one and two variants, respectively. Genotype CSFV-2 was represented by the Spanish ovine isolate 5440/99 and the genotype CSFV-3 included the Japanese strains Okinawa/86 and Kanagawa/74. CSFV genotypes revealed a strong relationship with Border disease virus strains, showing relatively low divergence values when compared to other pestivirus species. Evaluation of nucleotide base pair divergence among genotypes and expression of evolutionary changes in the CSFV species led to the construction of a phylogenetic tree based on secondary structure.